Karyomorphological contribution to the genus Bellevalia (Asparagaceae) in Turkey - Demirci Kayıran, Serpil; Özhatay, Neri?Man (Pakistan Botanical Society, 2017)
As part of the karyological studies of the Asparagaceae grow in the Kahramanmaraş province, chromosome number and chromosomes morphology of three Bellevalia species have been determined: B. macrobotrys 2n= 8; B. gracilis 2n= 8, 16, B. tauri 2n= 8. This is the first karyotype reconstruction for B. macrobotrys. B. tauri is an endemic species to Turkey. Photographs of the mitotic metaphase plates and drawings with the idiograms are given. Additionally, idiograms and karyotypes of the species were performed by the use of Cameram© software. © 2017, Pakistan Botanical Society. All rights reserved.
Keywords: B. gracilis; B. macrobotrys; B. tauri; Bellevalia; Karyotype; Southern Anatolia; Turkey